2009
DOI: 10.1080/00207450802328250
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Levels of Food Restriction on Passive-Avoidance Memory and The Expression of Synapsin I in Young Mice

Abstract: The present study investigated the effects of food restriction (FR) on memory and the expression of synapsin I in the brain of young mice. The results showed that 20% FR did not retard the body weight gain of mice, while the 60% and 80% FR reduced the mice's body weight. The memory after 24 hr of learning was not changed by FR, whereas long-term memory was improved significantly in 20% FR mice. In addition, 60% and 80% FR did not impair the mice's memory. The transcriptional expression of synapsin I in mice br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
1
11
1
Order By: Relevance
“…Although, in this study, resveratrol was used as a caloric restriction mimetic to stimulate caloric restriction, the results obtained on the effect of resveratrol as CR mimetic on memory of mice were in corroboration with the findings of Deng et al [26] who reported no significant change in short-term memory of mice using the passive avoidance test for memory after subjecting mice to a 20% caloric restriction for one month. However, no uniform conclusion has been reached on the effect of caloric restriction or caloric restriction-like effects on cognitive functions in young animals.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Although, in this study, resveratrol was used as a caloric restriction mimetic to stimulate caloric restriction, the results obtained on the effect of resveratrol as CR mimetic on memory of mice were in corroboration with the findings of Deng et al [26] who reported no significant change in short-term memory of mice using the passive avoidance test for memory after subjecting mice to a 20% caloric restriction for one month. However, no uniform conclusion has been reached on the effect of caloric restriction or caloric restriction-like effects on cognitive functions in young animals.…”
Section: Discussionsupporting
confidence: 78%
“…Nevertheless, some investigators have suggested that caloric restriction enhanced learning and memory in young animals [27,41,42], while others reported the contrary [28,43]. This discrepancy was attributed to several factors including differences in caloric restriction treatment, duration of caloric restriction, species or strain of animal, and type of behavioural test [26].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…There are, nevertheless, alternative explanations of the persistent CPP that cannot be ruled out at this time. For example, food restriction may enhance recall of the cocaine-context association (Hashimoto and Watanabe, 2005; Deng et al, 2009) or impair extinction learning or its expression (Koot et al, 2009). However, in both Experiments 1 and 3 food-restricted subjects were not only resistant to extinction of the CPP but displayed trends indicative of CPP sensitization.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoreactivity for synapsin I increase during LTP (Sato et al 2000); Likewise, spatial learning in the Morris water maze induced synapsin I mRNA and protein expression (Gomez-Pinilla et al 2001). Moreover, absence of synapsin I resulted in the decrease of vesicular transport of specific neurotransmitters in mice brain (Bogen et al 2006(Bogen et al , 2009 In a recent report by Deng et al (2009) it was shown that gene expression of synapsin I in mice brain was up-regulated by 4 weeks of 20% food restriction, which also significantly improved the memory of mice, whereas, synapsin I gene expression was down-regulated by 60 and 80% food restriction with no effect on memory. These results are in agreement with our present findings that DR reverses the age-related decline in the levels of synapsin 1 in old rats.…”
Section: Late-onset Dr Enhance Cellular Stress Response and Preservesmentioning
confidence: 95%